2017
DOI: 10.7717/peerj.3862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astragalus polysaccharide on the adhesion-related immune response of endothelial cells stimulated with CSFVin vitro

Abstract: BackgroundAstragalus polysaccharide (APS) has immunomodulatory activities on porcine peripheral blood mononuclear cells. The immunomodulatory effects of APS on porcine endothelial cells (ECs) expose to classical swine fever virus (CSFV) remain unknown.MethodsThe virus was titrated using an indirect immune biotin enzyme standard method to confirm that porcine ECs were susceptible to CSFV infection and to determine the TCID50 of CSFV (C-strain). Porcine ECs were cultured with CSFV in the presence of APS. Relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In recent years, research has mainly focused on polysaccharides obtained from Chinese medicinal herbs due to their value as novel immune adjuvants against infections ( 34 , 35 ). For example, Astragalus polysaccharides (APS) was evaluated for its potential as an effective adjuvant in vaccines against Porcine reproductive and respiratory syndrome virus (PRRSV) or CSFV, and demonstrated that APS had immunomodulatory effects on pig peripheral blood mononuclear cells exposed to PRRSV or CSFV ( 36 , 37 ). PTFP has been proven to enhance the immune effectiveness of Newcastle disease vaccine in chickens ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research has mainly focused on polysaccharides obtained from Chinese medicinal herbs due to their value as novel immune adjuvants against infections ( 34 , 35 ). For example, Astragalus polysaccharides (APS) was evaluated for its potential as an effective adjuvant in vaccines against Porcine reproductive and respiratory syndrome virus (PRRSV) or CSFV, and demonstrated that APS had immunomodulatory effects on pig peripheral blood mononuclear cells exposed to PRRSV or CSFV ( 36 , 37 ). PTFP has been proven to enhance the immune effectiveness of Newcastle disease vaccine in chickens ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Astragalus , a large genus of herbs, belongs to the legume family Fabaceae and has potent immune boosting and health-promoting properties ( 18 , 19 ). Astragalus membranaceus (AM) has been widely used for thousands of years in China to treat asthma.…”
Section: Introductionmentioning
confidence: 99%